The Government's Responsibility for Compensation for Land Procurement in Infrastructure Development Based on Act No. 2 of 2012 - Naomy Soegianto; Muh Afif Mahfud (Law Development Journal, 2023)
In the process of land acquisition, there will be many conflicts. In land acquisition, of course, the government will compensate landowners as a form of responsibility. Land acquisition in the process of construction for the public interest, basically must always sacrifice personal interests, with limited land availability. In the process of developing land acquisition on the Batang – Semarang Toll Road, there were several obstacles that hindered the smooth process of land acquisition, but with these obstacles the land acquisition team was able to handle it properly. This study aims to analyze the government's efforts in providing compensation for land acquisition, as well as countermeasures for communities who do not approve of the provision of compensation due to several things that deviate from Act No. 2 of 2012. The method used in this study is a normative juridical approach method. The results showed that the government in measuring land must be based on up to date data. The government should be more transparent to citizens about land valuation prices. In the case of the Batang - Semarang Toll Road, the government must still refer to Article 1 paragraph (2) of Act No. 2 of 2012 and Article 18 of the BAL. In the case of the Batang – Semarang Toll Road, the government must first negotiate by submitting compensation objections to the District Court and the Supreme Court. Then if you feel that you have not found an agreement, it can be taken by consignment based on Article 18 of the UUPA.